The Relationship Between the Knowledge of Pregnant Women and The Impact of Smoking on Pregnancy - Barreto Amaral, Meriana; Komanng Satriyasa, Bagus; Guterres Correia, Avelino; Suave Barreto, Celsea (Rifa'Institute, 2024)
Introduction: The prevalence of smoking in Timor-Leste, based on data from the Ministry of Health's 2016 survey, highlights that 53.7% of adults aged 15 to 49 were active smokers. Although this shows a reduction from 70% in 2009, cigarette consumption remains significant. For pregnant women who smoke, there are severe consequences for fetal health, including reduced fetal weight, premature birth, and increased risks of miscarriage, fetal mortality, and sudden infant death. Additionally, smoking during pregnancy can negatively affect the physical and intellectual development of children as they grow. Objective: Want to know the relationship between the knowledge of pregnant women and the impact of smoking on pregnancy at the Comoro Health Center, Post administrative Dom Aleixo, Dili Municipality, Timor-Leste. Method: The method for this research is quantitative with the type of research of analytical observation with cross-sectional approach with non-probability sampling technique with accidental sampling method. Result and Discussion: The result of the study is the relationship between the knowledge of pregnant women and the impact of smoking on pregnancy (p-value: 0,001). Conclusion: The results of the study indicate that there is a relationship between the knowledge of pregnant women and the impact of smoking on pregnancy.